Pengaruh Faktor Lingkungan terhadap Kejadian Tuberkulosis Paru di Wilayah Kerja Puskesmas Kedaton Bandar Lampung - Safitri, Devi Nilam Laila; Putri, Devita Febriani; Amirus, Khoidar; Nuryani, Dina Dwi; Ekasari, Fitri (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Tuberculosis is a disease caused by Mycobacterium tuberculosis. The number of TB cases at the Kedaton Community Health Center in 2020 was 271 cases, in 2021 there were 193 cases, in 2022 there were 250 cases. Objective to determine the influence of environmental factors on the incidence of pulmonary tuberculosis in the working area of the Kedaton Bandar Lampung health center. This study used a case control design with 148 samples. In univariate statistical tests, bivariate chi-square, and multivariate logistic regression.In the univariate test results low income was 116 (78.4%), residential density met the requirements 85 (57.4%), ventilation did not meet the requirements 95 (64.2%), humidity met the requirements of respondents 81 (54.7%), temperature does not meet requirements 82 (55.4%), lighting does not meet requirements 76 (51.4%). Bivariate test results for variables that have a significant relationship with the incidence of pulmonary tuberculosis are residential density p-value 0.008, ventilation p-value 0.006, humidity p-value 0.003, temperature p-value 0.005, lighting p-value 0.000, while income does not have a significant relationship. p-value 0.550. The results of the multivariate analysis test showed that the dominant factor in the incidence of pulmonary tuberculosis was lighting (OR 5.759). Conclusion there is no significant relationship between income and the incidence of pulmonary tuberculosis, there is a significant relationship between residential density, ventilation, humidity, temperature and lighting and the incidence of tuberculosis. The dominant factor in the incidence of pulmonary tuberculosis is lighting. Keywords: Risk Factors, Home Environmental Health, Pulmonary Tuberculosis  ABSTRAK Tuberkulosis adalah penyakit yang disebabkan Mycobacterium tuberkulosis. Jumlah kasus tuberculosis di Puskesmas Kedaton tahun 2020 berjumlah 271 kasus, tahun 2021 berjumlah 193 kasus, tahun 2022 berjumlah 250 kasus.Tujuan penelitian ini mengetahui pengaruh faktor lingkungan terhadap kejadian tuberkulosis paru di wilayah kerja puskesmas Kedaton Bandar Lampung. Penelitian ini menggunakan desain case control dengan 148 sampel. Di uji statistik univariat, bivariat chi-square, dan multivariat regresi logistic. Pada hasil uji univariat pendapatan rendah 116 (78,4%), kepadatan hunian yang memenuhi syarat 85 (57,4%), ventilasi yang tidak memenuhi syarat 95 (64,2%), kelembaban yang memenuhi syarat responden 81 (54,7%), suhu yang tidak memenuhi syarat 82 (55,4%), pencahayaan tidak memenuhi syarat 76 (51,4%). Hasil uji bivariat variabel yang memiliki hubungan bermakna dengan kejadian tuberculosis paru yaitu kepadatan hunian p-value 0,008 ventilasi p-value 0,006, kelembaban p-value 0,003, suhu p-value 0,005, pencahayaan p-value 0,000, sedangkan yang tidak memiliki hubungan bermakna yaitu pendapatan p-value 0,550. Hasil uji analisis multivariat menunjukkan faktor dominan terhadap kejadian tuberkulosis paru adalah pencahayaan (OR 5,759). Kesimpulannya tidak terdapat hubungan bermakna antara pendapatan dengan kejadian tuberkuosis paru, terdapat hubungan bermakna antara kepadatan hunian, ventilasi, kelembaban suhu dan pencahayaan dengan kejadian tuberculosis. Factor dominan terhadap kejadian tuberkulosis paru adalah pencahayaan. Kata Kunci: Faktor Risiko, Kesehatan Lingkungan Rumah, Tuberkulosis Paru